AIDS: ethical problems in married life - Ciccone, Lino (Medicina e Morale, 1992)
The article deals with some of the ethical problems caused by AIDS in the field of sexuality. After a brief introduction that explains the methodology, the author, a moral theology lecturer, concentrates on some fundamental truths regarding the sexual morality of married couples. He then deals in particular with the moral problems in the sexual life of married couples and moral problems for engaged people, specially in relation to sieropositivity.